PENGEMBANGAN BUKU AJAR PARTIKEL MATERI BERBASIS REPRESENTASI KIMIA - Agung Widi Utomo; Noor Fadiawati; Ila Rosilawati (Universitas Lampung, 2013)
This research aims to develop a matter particle textbook based on the chemistry representation and to describe the characteristics, the teachers’ responses, and the students’ responses toward the matter particle textbook based on the chemistry representation, and to know the obstacles encountered in developing a matter particle textbook based on the chemistry representation. The research used Research and Development method. Based on the teachers’ and students’ responses, it showed the content suitability of the textbook and curriculum is very high. It is about 95%. The graphic/the attractiveness aspect of the textbook is also very high about 94%, and the readable aspect of the matter particle textbook based on the chemistry representation is also very high about 93,04%. Both students and the teachers are gave positive responses to developed Integrated Science textbook.Penelitian ini bertujuan untuk mengembangkan buku ajar partikel materi berbasis representasi kimia, serta mendeskripsikan karakteristik, tanggapan guru, respon siswa terhadap buku ajar partikel materi berbasis representasi kimia, dan mengetahui kendala-kendala yang ditemui ketika mengembangkan buku ajar partikel materi berbasis representasi kimia. Metode penelitian yang digunakan adalah metode Penelitian dan Pengembangan. Dari hasil tanggapan guru dan siswa diperoleh data bahwa kesesuaian isi buku ajar dengan kurikulum sangat tinggi sebesar 95%, aspek grafika/kemenarikan buku ajar sangat tinggi sebesar 94%, dan tingkat keterbacaan buku ajar partikel materi berbasis representasi kimia ini sangat tinggi sebesar 93,04%. Siswa dan guru merespon baik buku ajar IPATerpadu yang dikembangkan.Kata kunci :buku ajar, partikel materi, representasi kimia.